2022
DOI: 10.3390/jcm11123299
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Dysfunction Is Associated with Decreased Nitric Oxide Bioavailability in Dysglycaemic Subjects and First-Degree Relatives of Type 2 Diabetic Patients

Abstract: Oxidative stress plays an important role in the pathogenesis of diabetes. We investigated oxidative stress and nitrite/nitrate concentrations at baseline and during postprandial hyperglycaemia in 40 first-degree relatives (FDRs) of diabetic patients with normal oral glucose tolerance test (OGTT) results, 40 subjects with abnormal OGTT results (dysglycaemic) and 20 subjects with normal OGTT results (normoglycaemic). Malondialdehyde (MDA), protein carbonyls (PCs), nitrite/nitrate plasma levels, the perfused boun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…NO has a significant function in regulating synaptogenesis and neurotransmission in the central and peripheral nervous system [ 242 ]. There is evidence that basal NO production and NO bioavailability are reduced in diabetic patients [ 17 ]. Oghbaei et al [ 243 ] used a ureazotocin-induced diabetic male rat model to demonstrate that long-term supplementation with DN can affect testicular function and structure in these rats through the hypothalamic–pituitary–gonadal axis, thereby improving fertility parameters.…”
Section: Effect Of Bacteria With Nitrate Reductase In the Human Micro...mentioning
confidence: 99%
See 1 more Smart Citation
“…NO has a significant function in regulating synaptogenesis and neurotransmission in the central and peripheral nervous system [ 242 ]. There is evidence that basal NO production and NO bioavailability are reduced in diabetic patients [ 17 ]. Oghbaei et al [ 243 ] used a ureazotocin-induced diabetic male rat model to demonstrate that long-term supplementation with DN can affect testicular function and structure in these rats through the hypothalamic–pituitary–gonadal axis, thereby improving fertility parameters.…”
Section: Effect Of Bacteria With Nitrate Reductase In the Human Micro...mentioning
confidence: 99%
“…With the increase in microbiological studies and advances in high-throughput sequencing technology in recent years, several publications on the contribution of microbiota in systemic health and the underlying mechanisms of action have emerged [ 1 5 ]. Among them, the bacteria with nitrate reductase are also gaining popularity among researchers [ 6 ], which can affect the systemic health and disease of the host by regulating nitrate metabolism [ 7 ] (including digestive system [ 8 11 ], cardiovascular system [ 12 14 ], endocrine system [ 15 17 ], nervous system [ 18 20 ], respiratory system [ 21 23 ] and urinary tract-related diseases [ 24 26 ]). There are symbiotic bacteria with NRA (such as micropore bacteria, actinomycetes, Escherichia coli , etc.)…”
Section: Introductionmentioning
confidence: 99%
“…The glycocalyx likely plays a major role in the pathogenesis of cardiovascular complications in diabetes, such as diabetic retinopathy, cardiomyopathy, and nephropathy. In the absence of overt cardiovascular disease, glycocalyx barrier function is impaired following an oral glucose tolerance test in individuals with impaired glucose tolerance or first-degree relatives of patients with diabetes [24]. Moreover, impaired glycocalyx barrier function is accompanied by a low nitrite/nitrate plasma levels, implying an acute endothelial dysfunction.…”
Section: Diabetesmentioning
confidence: 99%
“…Interestingly, in the current Special Issue, Ikonomidis et al demonstrated that decreased nitric oxide bioavailability during postprandial hyperglycemia is linked to impaired endothelial, coronary and left ventricular myocardial function in dysglycaemic subjects and first-degree relatives of diabetic patients. Authors suggested that prolonged and repeated hyperglycaemia may play an important role in the development of atherosclerosis [3]. In fact, traditional cardiovascular risk factors, namely hypertension, hyperlipidemia, diabetes mellitus, metabolic syndrome and chronic smoking, are characterized by increased oxidative stress burden [4].…”
mentioning
confidence: 99%